Mendengarkan Adat Batak Toba: Berteologi Kontekstual tentang Adanya Keyakinan Relasi Orang Hidup dengan Roh Leluhur - Estomihi, Estomihi; Wibowo, Wahyu Satria; Singgih, Emanuel Gerrit (Institut Agama Kristen Negeri Tarutung, 2025)
This study is a contextual theological inquiry rooted in the spiritual tension experienced by Batak Toba Christians, who navigate between church prohibitions against engaging with ancestral spirits and their continued participation in cultural rites such as ziarah kubur (grave visitation) and mangongkal holi (exhumation ritual). The study seeks to reinterpret this tension theologically by adopting a posture of “listening” to local culture as an integral act of doing theology. “Listening” is understood not merely as empathetic openness, but as a theological act that creates space for transformative dialogue between the Gospel and indigenous tradition. Using a qualitative, literature-based approach with narrative-hermeneutic and reflective analysis, the research draws on Stephen B. Bevans’ Synthetic Model and the contextual insights of Imanuel Martasudjita. The findings suggest that Batak Toba rituals can be interpreted as means of grace, where believers encounter God within their historical and communal life. This study contributes to Indonesian contextual theology by integrating faith, culture, and Christian doctrine through an interpretive hermeneutic lens.